PELATIHAN PENERAPAN KAIDAH BAHASA INDONESIA DALAM TEKS IBADAH LIVE-STREAMING - Mawene, Aleda; Smas , Musa Hefer (JURNAL PENGABDIAN PAPUA, 2023)
This community service is focused in live-streaming worship text, which are the scipts broadcasted during virtual worship. Early surveys showed that there were still inconsistencies in the application of Bahasa Indonesia principles to those live-streaming worship text. By those reason, project consist of training, mentoring and monitoring were carried out 2 times. That project was carried out for two weeks through mentoring. The method used were Pakem and Inquiry. The techniques were question and answer, brainstorming, simulation and guided exercises. Evaluation was carried out through procject assignment in the form of text editing of 300 texts of Kidung Jemaat (or Song of Congregation). The results of the training project showed that the level of text editing completion for team A was considered successful. That level of completion in the first mentoring reached 70% with the participants’ level of understanding of the material reached 85% or in the good category. There was also a significant enhancement and better comprehension in second training. The assigments completion level rate was 100% with the success rate reached 95% or in very good category. This score was above the target score of 80% success. In conclucion, the traning and mentoring succeed to improve the capability of Church Multimedia team in applying the correct Bahasa Indonesia principles in the broadcasted slides and scripts during live-streaming worship.    Keywords: bahasa Indonesia principles; worship text; live-streaming